Assessment of the Provision of Quality Midwifery Care Service at Women’s and New Born Hospital, Lusaka Using a Modified Servqual Scale - Nankamba, Namayipo; Mwanaumo, Erastus (Journal of Health, Medicine and Nursing, 2025)
Purpose: The aim of the study was to assess the quality of midwifery care service provided to women by midwives at Women and New-Born Hospital (WNBH) in Lusaka District of Zambia using a modified SERVQUAL scale questionnaire. The study intended to evaluate the quality of the service from the viewpoint of service providers and recipients of the service (Women). Methodology: The research design was a non-experimental design utilisation a quantitative cross-sectional method. Systematic sampling was used to select 385 women and 185 midwives from the various health units. Quantitative data was analysed by employing descriptive statistics using the IBM Statistical Package for Social Sciences (SPSS) version 24. Chi-square and Fisher’s exact was conducted to test statistical significance between the independent and dependent variables. Findings: Majority of women (321, 83.4%) mentioned that midwives provide poor quality of midwifery service while majority of midwives (183, 99.5) termed their quality service level as fair. The service quality gap between the perceived and expected quality service from the SERVQUAL questionnaire ranged from 0 to -15 for all the dimensions under study showing that standards were not reached. Unique Contribution to Theory, Practice and Policy: Utilizing the SERVQUAL (service quality) theoretical model the research sought to identify service quality gaps which could enhance customer satisfaction if addressed. Recommendation includes a targeted effort by health facility to improve service quality through in-depth look at the tangibility, assurance, responsiveness, empathy and reliability dimensions of service quality. Quality should be a concern of every health care provider in the delivery system. Health institutions in Zambia, should make it as a mandate to understand client’s quality expectations in order to meet their quality needs leading to improved patient’s satisfaction, and ultimately increased facility utilization.